A new species of Afropinnotheres Manning, 1993 (Crustacea, Brachyura, Pinnotheridae) from southwestern India, the first record of the genus from the Indian Ocean, with a review of the Pinnotheridae of India and adjacent seas - Ng, Peter K. L.; Kumar, Appukuttannair Biju (Zootaxa, 2015)
A new species of pinnotherid crab of the genus Afropinnotheres Manning, 1993, is described from the brown mussel, Perna perna (Linnaeus, 1758), in southwestern India. This is the first record of the genus from the western Indian Ocean, the other four species been recorded from the eastern Atlantic. The new species can be distinguished from all congeners in  possessing a more rounded male carapace, form of the chela, relatively longer ambulatory legs which have no natatory setae, presence of dense pubescence on the male ambulatory legs, and the shape of the male and female telsons. The Indian Pinnotheridae is also reviewed and the taxonomy of the species reappraised. The taxonomy of Pinnaxodes Heller, 1865, and Holothuriophilus Nauck, 1880, is also discussed, in the context of their similarity to Afropinnotheres.